2013
DOI: 10.1177/084456211304500302
|View full text |Cite
|
Sign up to set email alerts
|

Health Inequities Experienced by Aboriginal Children with Respiratory Conditions and Their Parents

Abstract: Asthma and allergies are common conditions among Aboriginal children and adolescents. The purpose of this study was to assess the health and health-care inequities experienced by affected children and by their parents. Aboriginal research assistants conducted individual interviews with 46 Aboriginal children and adolescents who had asthma and/or allergies (26 First Nations, 19 Métis, 1 Inuit) and 51 parents or guardians of these children and adolescents. Followup group interviews were conducted with 16 adolesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(44 citation statements)
references
References 35 publications
1
43
0
Order By: Relevance
“…Our Phase 1 and 2 results ( 15 ) indicated that Mi’kmaq children living with asthma relied on peer as well as parental support, which is consistent with asthma support strategies for children in general ( 20 ). Given this finding, Phase 3 professional participants recognized that, in addition to educating school staff, educating the entire student population was important for building awareness and support and because children tend to share what they learn at school with their family members at home.…”
Section: Discussionsupporting
confidence: 70%
“…Our Phase 1 and 2 results ( 15 ) indicated that Mi’kmaq children living with asthma relied on peer as well as parental support, which is consistent with asthma support strategies for children in general ( 20 ). Given this finding, Phase 3 professional participants recognized that, in addition to educating school staff, educating the entire student population was important for building awareness and support and because children tend to share what they learn at school with their family members at home.…”
Section: Discussionsupporting
confidence: 70%
“…1 In the Northern Territory (NT), respiratory illness is the most frequent reason for hospitalisation of young children (<5 years) and preventable cause of death of Indigenous infants. 3,4 Health education is a key component in improving clinical outcomes. 3,4 Health education is a key component in improving clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Another limitation of our study is that there is an important difference between access to care and utilization of care. We were not able to disentangle this issue, and previous research has suggested that, even in Ontario, there may be barriers to utilization of care for Aboriginal patients . Future research into utilization of pediatric oncology care among minority and marginalized populations in Canada is required.…”
Section: Discussionmentioning
confidence: 86%
“…We were not able to disentangle this issue, and previous research has suggested that, even in Ontario, there may be barriers to utilization of care for Aboriginal patients. 37,43 Future research into utilization of pediatric oncology care among minority and marginalized populations in Canada is required. Finally, our data set did not contain information regarding adherence to therapy.…”
Section: Discussionmentioning
confidence: 99%